Racial and Ethnic Disparities in COVID‐19 Infections and Deaths Across U.S. Nursing Homes - Yue Li; Xi Cen; Xueya Cai; Helena Temkin‐Greener (2020)
To determine racial/ethnic disparities in weekly counts of new COVID-19 cases and deaths among nursing home residents or staff.Cross-sectional analysis of national nursing home COVID-19 reports linked to other data. Multivariable two-part models modeled disparities in count of cases or deaths, and logistic regressions modeled disparities in self-reported shortages in staff and personal protective equipment (PPE), across nursing home groups with varying proportions of racial/ethnic minority residents, defined as low-, medium-, medium-high-, and high-proportion groups.A total of 12,576 nursing homes nationally.None.None.Numbers of incident COVID-19 confirmed cases among residents and staff, and incident COVID-19 related deaths among residents (primary outcomes); and nursing home reported shortages in staff and PPE (secondary outcomes). All outcomes were reported for the week of May 25, 2020.The number of weekly new COVID-19 confirmed cases among residents ranged from an average of 0.4 cases per facility (standard deviation (SD) = 2.5) for the low-proportion group (93.0% had zero new cases) to 1.5 cases per facility (SD = 6.3) for the high-proportion group (78.9% had zero new cases). Multivariable regression estimated that compared with the low-proportion group, the likelihood of having at least one new resident case was 76% higher (odds ratio = 1.76; 95% confidence interval = 1.38-2.25; P = .000) for the high-proportion group. Similar across-facility disparities were found for the weekly count of new COVID-19 deaths among residents (ranging from 0.1 deaths per facility (SD = 1.1) for the low-proportion group to 0.4 deaths (SD = 2.0) for the high-proportion group) and in the weekly count of new COVID-19 confirmed cases among staff (ranging from 0.3 cases (SD = 1.4] to 1.3 cases (SD = 4.4) per facility). No substantial disparities in self-reported shortages of staff or PPE were found.Nursing homes caring for disproportionately more racial/ethnic minority residents reported more weekly new COVID-19 confirmed cases and/or deaths. Immediate actions are needed to address these system-level disparities.